High Solid Fluorescence of a Pyrazoline Derivative through Hydrogen Bonding - Liang Zhang (Molecules, 2017)
Pyrazoline and its derivatives often exhibit strong emissions in dilute solutions, but their emission intensity is often dramatically reduced in the solid state due to strong intermolecular interactions between neighboring molecules. In this report, we successfully synthesized a new pyrazoline 4-(3-(4-(decyloxy)phenyl)-1-(2,3,5,6-tetrafluoro-4-(trifluoromethyl)phenyl)-4,5-dihydro-1H-pyrazol-5-yl)-N,N-diethylaniline (PPDPD), into which seven fluorine (F) atoms were incorporated. In the solid state, PPDPD emits a strong blue light at λmax 430 nm with a fluorescence quantum yield of up to 41.3%. Single-crystal analysis showed the presence of intra/intermolecular C-H···F bonds that may impede molecular motion and block the non-radiative decay channel. Compound PPDPD therefore shows high emission efficiency in the solid state.